Dental care in Europe: financing, coverage and provision. (30th September 2020) - Winkelmann, J; Henschke, C; Scarpetti, S; Panteli, D
Abstract: Background: In Europe, countries have adopted very different approaches to providing publicly subsidized dental insurance coverage. However, little attention has been paid on these variations in the coverage, financing and provision of oral health care and its implications. This cross-country Health Systems in Transition (HiT) Review aims to fill this gap in the field of comparison of oral health systems. Methods: The comparative HiT draws on multiple data sources. It builds on detailed country information from national HiTs and other international sources (MISSOC, OECD/OBS country profiles). International databases (Eurostat, OECD, EHIS, EU-SILC) are used as main sources to compare available oral health related indicators. National and international policy documents and information by country experts complement this information. The HiT covers all EU members states and countries belonging to the EU's single market (UK, Iceland, Norway, Switzerland). Results: In almost all countries, dental care is funded to a greater extent by private patient payments than other health care sectors. Overall, contribution of voluntary health insurances (VHI) to dental spending is low, while out-of-pocket spending is substantial in many countries leading to high levels of unmet needs for dental care for financial reasons, mainly for poor households. Comparison of coverage reveals that most countries commit to a minimum scope of basic dental care (emergency care, children), but there is large variation in terms of restriction of service packages ranging from countries with very limited, partial to comprehensive coverage. Conclusions: Dental care has become a priority for European policy makers as countries extend statutory dental care coverage recognising the importance of prevention of oral diseases. However, there remain wide variations in the level of coverage resulting in differences of likelihood of dental care use.